Method for growing nitrogen doped single crystal silicon ingot using continuous czochralski method, and single crystal silicon ingot grown by this method

JP2025026808AActive Publication Date: 2025-02-25GLOBALWAFERS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024189819
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2024-10-29
Publication Date
2025-02-25
Estimated Expiration
2040-08-04

AI Technical Summary

Benefits of technology

【0025】 もう一つの態様において、本開示は、本体部を有する単結晶シリコンインゴットに指向され、ここでは、本体部は、周囲縁、周囲縁と平行な軸長を有する中心軸、および中心軸から周囲縁まで延在する半径を有し、本体部は、単結晶シリコンインゴットの本体軸長の少なくとも40%にわたり、単結晶シリコンインゴットの本体軸長の少なくとも50%にわたり、単結晶シリコンインゴットの本体軸長の少なくとも60%にわたり、単結晶シリコンインゴットの本体軸長の少なくとも70%にわたり、または単結晶シリコンインゴットの本体軸長の少なくとも80%にわたり、平均本体抵抗率(または抵抗性、または固有抵抗:resistivity)を20%以下上回ってかつ20%以上下回って変化する抵抗率を有することを含む。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026808000001_ABST
    Figure 2025026808000001_ABST
Patent Text Reader

Abstract

To provide a method for growing a perfect silicon crystal.SOLUTION: A method for growing a single crystal silicon ingot by the continuous Czochralski method is disclosed. Melt depth and heat conditions are keeping a silicon melt constant during growth for continuously supplying the silicon melt while consuming the silicon melt and fixing a crucible position. A critical v / G is determined by a hot zone constitution; a continuous supplement of silicon to the melt during the growth can grow an ingot at a fixed pulling speed consistent with the critical v / G while growing the substantive part of an ingot main body; and the continuous supplement of silicon is achieved by periodical or continuous nitrogen addition producing a nitrogen doped ingot.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to U.S. Provisional Application Nos. 16 / 569,949 and 16 / 570,010, both filed September 13, 2019, the entire disclosures of which are incorporated herein by reference in their entireties.

[0002] FIELD OF THE DISCLOSURE The field of the disclosure relates to a method for growing a crystalline silicon ingot using a continuous Czochralski process and to a single crystal silicon ingot grown thereby. [Background technology]

[0003] (background) Single crystal silicon, the starting material for most processes in the fabrication of semiconductor electronic components, is commonly produced by the Czochralski ("Cz") process. In this process, polycrystalline silicon ("polysilicon") is introduced into a crucible and melted, and a seed crystal is brought into contact with the molten silicon and the single crystal is grown by slow extraction. After the formation of the neck is complete, the diameter of the crystal is expanded, for example, by decreasing the pulling rate and / or melt temperature until a desired or target diameter is reached. A cylindrical body of the crystal having an approximately constant diameter is then grown by controlling the pulling rate and melt temperature while compensating for the decrease in the melt level. Near the end of the growth process, but before the crucible is emptied of molten silicon, the crystal diameter is typically gradually reduced to form a tail end in the form of an end-cone. The end-cone is usually formed by increasing the crystal pulling rate and the amount of heat supplied to the crucible. The crystals are then separated from the melt when their diameter becomes small enough.

[0004] Czochralski growth techniques include batch Czochralski and continuous Czochralski. In batch CZ, a single polycrystalline charge is loaded into a crucible, and the single charge should be sufficient to grow a single crystal silicon ingot, after which the crucible is substantially depleted of silicon melt. In continuous Czochralski (CCZ) growth, polycrystalline silicon can be added continuously or periodically to the molten silicon to replenish the melt during the growth process, so that multiple ingots can be pulled from a single crucible during the growth process.

[0005] To carry out the CCZ process, conventional batch Czochralski growth chambers and equipment are modified to include a means for supplying additional polycrystalline silicon to the melt in a continuous or semi-continuous manner without adversely affecting the properties of the growing ingot. As seed crystals are continuously grown from the melt, solid polycrystalline silicon, such as granular polycrystalline silicon, is added to the melt to replenish the melt. The rate at which the additional solid polycrystalline silicon is added to the melt is typically controlled to maintain process parameters. To reduce the adverse effects of this replenishment activity on the concurrent crystal growth, conventional quartz crucibles are often modified to provide an outer or annular melting zone, into which additional material is delivered, in addition to the inner growth zone, into which the silicon ingot is pulled. These zones are in fluid communication with each other.

[0006] The continuously shrinking size of modern microelectronic devices imposes challenging restrictions on the quality of silicon substrates, which is substantially determined by the size and distribution of grown-in microdefects. Most microdefects formed in silicon crystals grown by the Czochralski (CZ) and Float Zone (FZ) processes are agglomerates of intrinsic point defects: silicon-vacancies and self-interstitials (or simply interstitials).

[0007] A series of studies established that interstitial agglomerates exist in two forms, namely, spherical interstitial clusters named B swirl defects (or B defects), and dislocation loops named A swirl defects (or A defects). Later discovered vacancy agglomerates, known as D defects, were identified as eight-sided spaces (or voids). Voronkov provided a widely accepted explanation for the microdefect distribution observed in silicon crystals based on the crystal growth conditions. According to Voronkov's model or theory, the temperature field near the melt / crystal interface drives the recombination of point defects and provides the driving force for their diffusion from the melt / crystal interface (where point defects exist at their respective equilibrium concentrations) into the crystal bulk. The interplay between the transport of point defects by both diffusion and convection and their recombination establishes the point defect concentration over a short distance from the interface, named the recombination length. Typically, the difference between the vacancy and interstitial concentrations beyond the recombination length, termed the excess point defect concentration, remains substantially constant away from the sides of the crystal. In rapidly pulled crystals, the spatial redistribution of point defects by their diffusion beyond the recombination length is generally insignificant - with the exception of regions close to the sides of the crystal which act as sinks or sources of point defects. Thus, if the excess point defect concentration beyond the recombination length is positive, vacancies remain in excess and agglomerate to form D defects at lower temperatures. If the excess point defect concentration is negative, interstitials remain the predominant point defects and agglomerate to form A and B defects. If the excess point defect concentration is below some detection threshold, no detectable microdefects are formed. Thus, typically, the type of growing microdefect is simply determined by the excess point defect concentration established beyond the recombination length. The process of establishing the excess point defect concentration is termed initial incorporation, and the predominant point defect species is termed incorporated predominant point defect.The type of incorporated point defect is determined by the ratio of the crystal pull rate (v) to the magnitude of the axial temperature gradient (G) near the interface. At higher v / G, the vacancy concentration at the interface is higher than the interstitial concentration, so that convection of point defects dominates their diffusion and vacancies remain the predominant incorporated point defect. At lower v / G, diffusion dominates convection, allowing the incorporation of fast diffusing interstitials as the predominant point defects. At v / G close to its critical value, both point defects are incorporated at very low comparable concentrations and mutually annihilate each other, thus suppressing the potential formation of any microdefects at lower temperatures. The observed spatial microdefect distribution can typically be explained by the radial non-uniformity of G and the change in v / G caused by the axial change in v. A striking feature of the radial microdefect distribution are oxide particles, which form in regions of relatively lower incorporated vacancy concentration via oxygen interaction with vacancies in a small range of v / G just above the critical v / G. These particles form narrow spatial bands that can be revealed by thermal oxidation as OSF (oxidation-induced stacking faults) rings. Quite often, the OSF rings mark the boundaries between adjacent vacancy-dominated and interstitial-dominated crystalline regions, known as V / I boundaries.

[0008] However, the microdefect distribution in CZ crystals grown at slower rates in many modern processes is influenced by the diffusion of point defects in the crystal bulk, including diffusion induced by the sides of the crystal. Thus, an accurate quantification of the microdefect distribution in a CZ crystal preferably incorporates two-dimensional point defect diffusion, both axially and radially. Quantification of only the point defect concentration field can qualitatively capture the microdefect distribution in a CZ crystal, since the type of microdefect formed is thereby directly determined. However, for a more accurate quantification of the microdefect distribution, it is necessary to capture the aggregation of point defects. Traditionally, the microdefect distribution is quantified by separating the initial incorporation of point defects and the subsequent formation of microdefects. This approach ignores the diffusion of dominant point defects near the nucleation region from higher temperature regions (where the microdefect density is negligible) to lower temperature regions (where the microdefects are present in higher density and consume the point defects). Alternatively, accurate numerical simulations based on predictions of the size distribution of the microdefect population at each location in the crystal are numerically expensive.

[0009] The transition between vacancy and interstitial dominated material occurs at a critical value of v / G, which is currently about 2.5×10 -5 cm 2 / sK. If the value of v / G exceeds a critical value, vacancies are the predominant intrinsic point defect, and the concentration of vacancies increases with increasing v / G. If the value of v / G is below the critical value, silicon self-interstitials are the predominant intrinsic point defect, and their concentration increases with decreasing v / G. Thus, process conditions such as growth rate (which affects v) and hot zone configuration (which affects G) can be controlled to determine whether the intrinsic point defects in single crystal silicon will be predominantly vacancies (v / G is typically greater than the critical value) or self-interstitials (v / G is typically less than the critical value).

[0010] In general, agglomerated defect formation occurs in two steps. First, defects called "nucleation" occur, which are the result of intrinsic point defects being supersaturated at a given temperature; above this "nucleation threshold" temperature, the intrinsic point defects remain soluble in the silicon lattice. The nucleation temperature for agglomerated intrinsic point defects is greater than about 1000° C.

[0011] Once this "nucleation threshold" temperature is reached, the native point defects agglomerate; i.e., precipitation of these point defects from the "solid solution" of the silicon lattice occurs. The native point defects will continue to diffuse through the silicon lattice as long as the temperature of the portion of the ingot in which they reside is maintained above a second threshold temperature (i.e., the "diffusion threshold"). Below this "diffusion threshold" temperature, the native point defects are no longer mobile within a commercially practical time period.

[0012] As long as the ingot remains above the "diffusion threshold" temperature, native point defects, either vacancies or interstitials, will diffuse through the silicon lattice to existing sites of agglomerated vacancy or interstitial defects, respectively, causing a given agglomerated defect to increase in size. Growth occurs as these agglomerated defect sites essentially act as "sinks," attracting and collecting native point defects due to their more favorable energy state for agglomeration.

[0013] Vacancy-type defects have been recognized as the origin of such crystalline defects observable as D defects, flow pattern defects (FPD), gate oxide integrity (GOI) defects, crystal-origin particle (COP) defects, as well as a class of bulk defects observed by infrared light scattering techniques such as scanning infrared microscopy and laser scanning tomography. Also present in the regions of excess vacancies are clusters of oxygen or silicon dioxide. Some of these clusters are small and remain relatively undistorted, causing virtually no harm to the vast majority of devices prepared from such silicon. Some of these clusters are large enough to act as nuclei for ring oxidation-induced stacking faults (OISFs). It has been speculated that this particular defect is promoted by previously nucleated oxygen aggregates catalyzed by the presence of excess vacancies. Oxide clusters form primarily during CZ growth below 1000° C. in the presence of moderate vacancy concentrations.

[0014] Self-interstitial related defects have been less studied. They are generally considered to be low density interstitial type dislocation loops or networks. Although such defects are not the cause of gate oxide integrity failure, which is a key wafer performance criterion, they are widely recognized as the cause of other types of device failures, usually related to leakage current problems.

[0015] In this regard, it should be noted that, generally speaking, oxygen in the interstitial form in the silicon lattice is typically considered to be a point defect in silicon rather than an intrinsic point defect, while silicon lattice vacancies and silicon self-interstitials (or simply interstitials) are typically considered to be intrinsic point defects. Thus, substantially all microdefects may be generally considered to be agglomerated point defects, while D defects (or voids), as well as A and B defects (i.e., interstitial defects), may be more particularly considered to be agglomerated intrinsic point defects. Oxygen clusters are formed by the absorption of vacancies; thus, oxygen clusters may be considered to be aggregates of both vacancies and oxygen.

[0016] Furthermore, the density of such vacancies and self-interstitial agglomerated point defects in Czochralski silicon has historically been estimated to be approximately 1×10 3 / cm 3 ~Approx. 1×10 7 / cm 3 while the density of oxygen clusters is approximately 1×10 8 / cm 3 ~1×10 10 / cm 3 It should be noted that agglomerated intrinsic point defects are therefore of rapid growth in importance to device manufacturers, as such defects can significantly impact the yield potential of single crystal silicon material in the production of complex advanced integrated circuits.

[0017] In light of the above, in many applications, it is preferred that some or all of the silicon crystals that are subsequently sliced ​​into silicon wafers are substantially free of these agglomerated native point defects. To date, several approaches have been reported for growing substantially defect-free silicon crystals. Generally speaking, all of these approaches involve controlling the v / G ratio to determine the initial type and concentration of native point defects present in the growing CZ single crystal silicon crystal. However, in addition, such approaches may involve controlling the subsequent thermal history of the crystal to allow extended diffusion times to suppress the concentration of native point defects therein, thus limiting or avoiding the formation of agglomerated native point defects in some or all of the crystal. (See, for example, U.S. Pat. Nos. 5,393,433, 5,393,621, 5,393,713, 5,393,725, and 5,496,732, the entire contents of which are incorporated herein by reference.) However, alternatively, such approaches may involve a rapidly cooled silicon (RCS) growth process, in which the subsequent thermal history of the crystal is then controlled to rapidly cool at least a portion of the crystal through a target nucleation temperature to control the formation of agglomerated native point defects in that portion. Alternatively, one or both of these approaches may allow at least a portion of the grown crystal to be maintained above the nucleation temperature for an extended period of time to reduce the concentration of native point defects prior to rapidly cooling this portion of the crystal through the target nucleation temperature, thus substantially limiting or avoiding the formation of agglomerated native point defects therein. (See, e.g., U.S. Patent No. 6,399,633, the entire disclosure of which is incorporated herein by reference.) Still further, methods have been developed to reduce or eliminate agglomeration of point defects from the center to the edges of the ingot by simultaneous control of the cooling rate of the solidified ingot and the radial variation of the axial temperature gradient near the interface (G). (See, e.g., U.S. Patent No. 6,399,633, the entire disclosure of which is incorporated herein by reference.)

[0018] Polished silicon wafers that meet the manufacturer's requirements for the absence of agglomerated point defects, e.g., crystal origin pits (COP), may be referred to as neutral silicon or full silicon. Full silicon wafers are preferred for many semiconductor applications, e.g., as a lower cost polished wafer alternative to wafers with higher epitaxial deposition. Over the past two decades, many silicon wafer suppliers have developed defect-free and COP-free wafer products in both 200mm and 300mm diameters for sale mostly to the memory (DRAM / NAND / FLASH) market, which has traditionally been more sensitive to cost pressures within the market. As customer application device nodes have shrunk, industry standards for acceptable defectivity have evolved over this time frame in terms of acceptable levels of light point scatter (LLS) and gate oxide integrity (GOI). For example, industrial COP-free specifications could once have been less than a few hundred at sizes below 0.12um. More current standards require a COP of less than 20 at sizes 0.026 μm or less to qualify as full silicon. As another example, the past standard for GOI in MOS transistors was 95% at ≤8 MV (B-mode). Currently, the specification has shifted to 99% at 10-12 MV (D-mode). On top of this requirement, the need for improved radial oxygen precipitation across the wafer, traditionally measured by BMD density (bulk microdefects) and BMD size distribution, is required as device nodes shrink to avoid substrate slip during processing or warp that can impact the overlay patterned during device lithography. As these specifications (LLS, GOI, BMD uniformity, etc.) have tightened, the control window for defect and COP free silicon growth has shrunk significantly, significantly lowering the crystal throughput of the process. This is because the acceptable band structure (which can be directly translated into the process window of operation) has changed over time in the specifications.

[0019] This section is intended to inform the reader of various aspects of art that may be relevant to the various aspects of the disclosure, which are described and / or claimed below. This discussion is believed to be helpful in providing the reader with background information to facilitate a better understanding of the various aspects of the disclosure. As such, these statements should not be read as admissions of prior art in this light. [Prior art documents] [Patent documents]

[0020] [Patent Document 1] U.S. Patent No. 6,287,380 [Patent Document 2] U.S. Patent No. 6,254,672 [Patent Document 3] U.S. Pat. No. 5,919,302 [Patent Document 4] U.S. Patent No. 6,312,516 [Patent Document 5] U.S. Patent No. 6,328,795 [Patent Document 6] US Patent Application Publication No. 2003 / 0196587 [Patent Document 7] U.S. Pat. No. 8,673,248 Summary of the Invention [Means for solving the problem]

[0021] (summary) One aspect of the present disclosure is directed to a method for producing a single crystal silicon ingot by a continuous Czochralski process, the method including: adding an initial charge of polycrystalline silicon to a crucible, the initial charge further comprising a nitrogen source; heating the crucible containing the initial charge of polycrystalline silicon and nitrogen source to form a silicon melt in the crucible, wherein the silicon melt comprises an initial volume of molten silicon and has an initial melt elevation level; contacting a silicon seed with the silicon melt; withdrawing the silicon seed to grow a neck, wherein the silicon seed is withdrawn at a neck pull rate during growth of the neck, and further comprising: 13 atoms / cm 3 pulling the silicon seed crystal to grow an outwardly flaring seed-cone adjacent the neck, wherein the silicon seed crystal is pulled at a seed-cone pull rate during growth of the outwardly flaring seed-cone, and further wherein the outwardly flaring seed-cone has a neck nitrogen concentration of at least about 1×10 13 atoms / cm 3 and pulling the silicon seed crystal to grow a main body of the single crystal silicon ingot adjacent the outwardly extending seed cone, wherein the silicon melt includes a volume of molten silicon and a melt height level during growth of the main body of the single crystal silicon ingot, and further wherein the main body of the single crystal silicon has a nitrogen concentration of at least about 1×10 13 atoms / cm 3wherein the single crystal silicon ingot body is grown at an initial variable body pull rate and a constant body pull rate, and the single crystal silicon ingot body is grown at the initial variable body pull rate for less than about 20% of the single crystal silicon ingot body length and at the constant body pull rate for a growth of at least about 30% of the single crystal silicon ingot body length; and further comprising: continuously or periodically supplying polycrystalline silicon to a crucible, thereby replenishing a volume of molten silicon in the crucible during growth of the single crystal silicon ingot body, thereby maintaining a melt height level; and continuously or periodically supplying a nitrogen source to the crucible, thereby replenishing the amount of nitrogen.

[0022] In another aspect, the disclosure is directed to a monocrystalline silicon ingot having a body portion, wherein the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the monocrystalline silicon ingot's body axial length, spanning at least 70% of the monocrystalline silicon ingot's body axial length, or spanning at least 80% of the monocrystalline silicon ingot's body axial length are characterized by non-detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I defects (A defects) by Secco etch technique.

[0023] In another aspect, the present disclosure is directed to a single crystal silicon ingot having a body, wherein the body has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, the body comprising interstitial oxygen at a body oxygen concentration that varies by no more than 20% above and no less than 20% below an average body oxygen concentration across at least 40% of the body axial length of the single crystal silicon ingot, across at least 50% of the body axial length of the single crystal silicon ingot, across at least 60% of the body axial length of the single crystal silicon ingot, across at least 70% of the body axial length of the single crystal silicon ingot, or across at least 80% of the body axial length of the single crystal silicon ingot.

[0024] In another aspect, the disclosure is directed to a single crystal silicon ingot having a body portion, where the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, the body portion comprising nitrogen at a body nitrogen concentration that varies no more than 20% above and more than 20% below an average body nitrogen concentration along at least 40% of the body axial length of the single crystal silicon ingot, along at least 50% of the body axial length of the single crystal silicon ingot, along at least 60% of the body axial length of the single crystal silicon ingot, along at least 70% of the body axial length of the single crystal silicon ingot, or along at least 80% of the body axial length of the single crystal silicon ingot.

[0025] In another aspect, the present disclosure is directed to a single crystal silicon ingot having a body portion, wherein the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, the body portion having a resistivity that varies no more than 20% above and more than 20% below an average body resistivity (or resistivity, or resistivity) over at least 40% of the single crystal silicon ingot's body axial length, over at least 50% of the single crystal silicon ingot's body axial length, over at least 60% of the single crystal silicon ingot's body axial length, over at least 70% of the single crystal silicon ingot's body axial length, or over at least 80% of the single crystal silicon ingot's body axial length.

[0026] Various refinements exist for the features noted in connection with the above-mentioned aspects of the disclosure. Also, additional features may be incorporated in the above-mentioned aspects of the disclosure as well. These refinements and additional features may exist individually or in any combination. For example, the various features discussed below in connection with any of the illustrated embodiments of the disclosure may be incorporated alone or in any combination in any of the above-mentioned aspects of the disclosure. [Brief description of the drawings]

[0027] [Figure 1] Figures 1A (early body growth), 1B (middle body growth), and 1C (late body growth) show melt volume or depth and crucible position as a function of crystal length during a typical batch Czochralski process. [Figure 2A] FIG. 2A is a graph showing the constant variation in pull rate required to achieve sufficient defectivity control in ingots grown by a typical batch Cz process. [Figure 2B] FIG. 2B is a graph showing the variation of nitrogen dopant concentration due to the segregation factor effect in ingots grown by a typical batch Cz process. [Diagram 3]FIG. 3 is a graph showing the pull rate profile required to achieve sufficient defectivity control in an ingot grown by a typical batch Cz process that includes the application of a magnetic field. [Figure 4A] FIG. 4A is a graph showing the pull rate profile required to achieve sufficient defectivity control in an ingot grown by a typical continuous Cz process according to the method of the present disclosure. [Figure 4B] FIG. 4B is a graph comparing nitrogen dopant concentrations between ingots grown by a typical batch Cz process and an ingot grown by a typical continuous Cz process according to the method of the present disclosure. [Diagram 5] FIG. 5 shows a typical crucible configuration suitable for a typical continuous Cz process according to the method of the present disclosure. [Figure 6] 6A, 6B and 6C show the melt level and ingot growth of a typical continuous Cz process according to the method of the present disclosure. [Figure 7] FIG. 7 is a graph illustrating a nitrogen source addition protocol to the melt for growing an exemplary continuous Cz process grown ingot according to the method of the present disclosure. [Figure 8] 8A and 8B show a magnetic field applied to a silicon melt during growth of an ingot by a typical continuous Cz process according to the method of the present disclosure.

[0028] Corresponding reference characters indicate corresponding parts throughout the drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] (Detailed Description) In the context of this disclosure, "perfect silicon" refers to a Czochralski-grown single crystal silicon ingot or a single crystal silicon wafer sliced ​​from a Czochralski-grown single crystal silicon ingot grown under conditions that meet or exceed the criteria of Perfect Silicon® (SunEdison Semiconductor, Ltd.). These criteria include ingots or wafers sliced ​​therefrom that meet or exceed industry specifications for agglomerated defects, DSOD (direct surface oxide defects), COP (crystal origin pits or particles), D-defects and I-defects, etc. For example, a "perfect silicon" wafer may be characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I-defects (A-defects) by Secco etch technique. The Secco etch (or etch) involves the application of a dilute aqueous solution of alkaline dichromate and hydrofluoric acid to adequately reveal dislocations and other lattice defects in the various crystallographic (100), (111) and (110) planes of silicon. The etch results in both lines (low angle grain boundaries) and slip lines. The disclosed method allows for the growth of whole silicon, e.g., single crystal silicon ingots including wafers sliced ​​from such ingots, over at least about 70% of the length of the single crystal silicon ingot, e.g., over at least about 80% of the length of the single crystal silicon ingot, or even over at least about 90% of the length of the single crystal silicon ingot.In some embodiments, wafers sliced ​​from ingots grown over at least about 60% of the body length of the monocrystalline silicon ingot, over at least about 70% of the body length of the monocrystalline silicon ingot, such as over at least about 80% of the body length of the monocrystalline silicon ingot, or even over at least about 90% of the body length of the monocrystalline silicon ingot, are characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown) and zero I defects (A defects) by Secco etch technique. In some embodiments, wafers sliced ​​from ingots grown over at least about 60% of the body length of the single crystal silicon ingot, over at least about 70% of the body length of the single crystal silicon ingot, such as over at least about 80% of the body length of the single crystal silicon ingot, or even over at least about 90% of the body length of the single crystal silicon ingot, are characterized by a GOI yield (i.e., non-failure) in MOS type transistors of 95% or more, preferably 99% or more at ≦8 MV (B-mode) and / or 95% or more, preferably 99% or more at 10-12 MV (D-mode). In some embodiments, wafers sliced ​​from an ingot grown over at least about 60% of the body length of the monocrystalline silicon ingot, over at least about 70% of the body length of the monocrystalline silicon ingot, such as over at least about 80% of the body length of the monocrystalline silicon ingot, or even over at least about 90% of the body length of the monocrystalline silicon ingot, with less than 20 COPs at 0.026 μm size or less to qualify as full silicon.

[0030] In the conventional batch Czochralski process for growing single crystal silicon ingots, both the melt / interface and thermal conditions of the crystal change continuously as a function of increasing ingot length due to the consumption of silicon melt and the variability of the crucible position during ingot growth. A depiction of melt depletion and crucible movement can be found in FIG. 1. FIGS. 1A (early body growth), 1B (middle body growth) and 1C (late body growth) show the melt level and crucible height as a function of crystal length during the batch Cz process. As the melt conditions, e.g., mass, height level and crucible position, are continuously changing during the batch process, the v / G ratio (growth rate V / axial temperature gradient G) required to minimize defectivity will continuously change the crystal length and alter the quality of the crystal. To maintain the desired quality to meet specifications within the process window, continuous controlled adjustment of several parameters is required depending on the position. These parameters include crucible rotation rate (C / R), seed rotation rate (S / R), seed lift rate (S / L), heater power, reflector height, etc. See FIG. 2A, which is a graph showing the constant variation in pull rate required to achieve sufficient defectivity control in ingots grown by a typical batch Cz process. The lines defined by the triangles (---▲---) are the ever-changing critical pull rates to achieve the critical v / G values. The pull rate can be varied within the upper critical pull rate ("UCL") indicated by the squares (---■---), and the lower critical pull rate ("LCL") indicated by the diamonds (---◆---), and still achieve acceptable defectivity control. These three lines represent pull rates that can produce perfect silicon. Within the upper and lower pull rate boundaries, perfect silicon with predominant intrinsic point defects can be produced. For example, when the applied pulling rate is controlled between the lines labeled with triangles and squares in FIG. 2A (as well as FIGS. 3 and 4), vacancy-dominated ("Pv") silicon is produced, and when the applied pulling rate is controlled between the lines labeled with triangles and diamonds in FIG. 2A (as well as FIGS. 3 and 4), interstitial-dominated ("Pi") silicon is produced.In the example depicted in FIG. 2A (as well as in FIGS. 3 and 4), in the early and middle portions of the ingot growth, full silicon may be grown with vacancy-dominated point defects, as shown by the representation of the ingot cross-sectional area labeled "Pv". FIG. 2A shows that the ingot is vacancy-dominated from the center to the edge. In the example shown in FIG. 2A, in the later portion of the growth, the ingot is characterized by regions of vacancy-dominated point defects and interstitial-dominated point defects, which are represented in the cross-sectional area region labeled "Pi". For example, an ingot may be grown that is interstitial-dominated from the center to a radial length less than the entire ingot radius, which is surrounded by a band of vacancy-dominated material to the edge of the ingot. Still, in the later portion, the cross-sectional area of ​​the ingot shows vacancy-dominated material in the center, which is surrounded by another band of vacancy-dominated material at the edge. These depictions are merely for illustrative purposes and are not intended to be limiting in the manner of the present disclosure. Perfect silicon, i.e., ingots and their riced wafers free of detectable agglomerated point defects, is due in part to proper control of excess point defects (vacancies and interstitials) by the ingot pull rate. Intrinsic point defects such as vacancies and interstitials occur in ingots grown by the Czochralski method. The presence of such defects has no impact on whether the silicon is perfect. Rather, perfect silicon is characterized as being free of agglomerated point defects such as COP, DSOD and I defects.

[0031] FIG. 2A (as well as FIGS. 3 and 4A) also shows the agglomerated defects that can occur in an ingot as a function of pull rate outside the upper and lower critical v / G limits at any crystal length. If the upper critical pull rate is exceeded (v / G is higher than the critical v / G), defects that can occur include DSOD (direct surface oxide defects) or COP (crystal-induced pits or particles). If the pull rate is below the lower critical pull rate (v / G is lower than the critical v / G), defects that can occur include I-defects. The bands in which these defects occur are also shown in the ingot cross-section. In regions where the predominant excess point defects are vacancies, agglomeration of vacancy defects forms bulk defects such as COPs, DSOD due to agglomeration and precipitation of vacancies during Cz silicon crystal growth and cool down. In regions where the predominant excess point defects are interstitial silicon atoms, they agglomerate to form bulk defects such as I defects due to the agglomeration / precipitation of interstitial silicon and punch out dislocations. Any small deviation in v / G will form defects due to the agglomeration of either vacancies or interstitial silicon atoms.

[0032] In addition to substrate defectivity control, wafer strength is another important variable for certain applications, such as FLASH devices, where higher wafer strength is more advantageous for vertical stacking of devices. In some technologies, wafer strength is provided by manipulation of oxygen deposition (or precipitation) and intrinsic gettering. For example, increasing the oxygen content in the wafer is the predominant method of manipulating oxygen deposition. In addition to or instead of oxygen content manipulation, the melt and the ingots grown therefrom can be doped with impurities such as nitrogen, which can manipulate both COP size and BMD density. Nitrogen doping can also provide a larger full silicon quality window relative to non-nitrogen doped material. Nitrogen doping can segregate axially during growth due to a segregation factor effect. The nitrogen segregation factor is less than unity, about 7×10 -4It has been reported that nitrogen does not partition preferentially into the growing ingot, which increases the nitrogen content in the melt during the ingot pulling process, thereby increasing the nitrogen content along the axial length of the growing monocrystalline silicon ingot. See FIG. 2B, which is a graph showing the increase in nitrogen concentration, which may be as much as seven times or more from the beginning of the ingot growth to the end of the ingot growth, along the axial length of the crystal prepared by the batch Czochralski method with melt conditions as shown in FIG. 1A-1C. The change in nitrogen axis due to the change in the position of the growing crystal as polysilicon is consumed, and the change in the crystal / melt interface and thermal conditions (see FIG. 1A-1C) are obstacles to maintaining good PS quality axially unless they are compensated for during growth through constant tuning of the crystal growth conditions. Because of this, v / G continuously changes the crystal length, which may change the quality of the crystal.

[0033] magnetic field , e.g., horizontal or Cusp (or Tip : cusp) magnetic field can be applied to modify the melt flow pattern within the crucible and allow for increased control of the shape and height of the crystal / melt interface, thereby enhancing quality control. However, pulling rates and other parameters must still be modified to achieve acceptable defectivity control, as illustrated in FIG. 3. FIG. 3 shows the effect of an applied magnetic field2B is a graph showing the pull rate profile required to achieve sufficient defectivity control in an ingot grown by a typical batch Cz process at 1000 K. The line defined by the triangles (---▲---) is the critical pull rate to achieve a critical v / G value, which is continuously varied, if necessary, during the growth of the single crystal silicon ingot. The pull rate can be varied within the upper critical pull rate ("UCL") indicated by the squares (---■---) and the lower critical pull rate ("LCL") indicated by the diamonds (---◆---) and still achieve acceptable defectivity control. The areas of native point defects and agglomerated point defects in the cross-sectional area of ​​the single crystal silicon ingot are substantially the same as those described above in the description of FIG. 2A.

[0034] According to the method of the present disclosure, single crystal silicon ingots are grown by the continuous Czochralski (CCZ) method under conditions that allow the melt depth (i.e., height level of the molten silicon) and thermal conditions to remain substantially constant during growth, since the melt is continuously replenished as it is consumed. In some embodiments, maintaining a substantially constant height level of the molten silicon allows the crucible to be maintained in a fixed position. Once v / G is fixed with a suitable hot zone configuration, the process window will be fixed (i.e., no control adjustments) over a substantial portion of the crystal length. Once the process conditions (S / R, power, gas flows and / or pressure, magnetic flux density, Cusp Gas flow, chamber pressure and C / R are used to control oxygen content once the HMCZ MGP position (or HMCZ MGP position) is set. Thus, the disclosed method enables the growth of single crystal silicon ingots by a continuous Czochralski (CCZ) method where the pull rate is constant during the growth of a substantial length of the ingot, and ingots grown by this method have consistent and acceptable defectivity control, O 2 , over a substantial portion of the axial length of the ingot. i It has uniformity, BMD uniformity and nitrogen content uniformity.

[0035] After all conditions are set to steady state, the pull rate to produce a single crystal silicon ingot with desired defectivity control over the entire crystal length will be constant and significantly reduced quality loss in production due to process control compared to conventional Cz processes. FIG. 4A is a graph of pull rate as a function of axial length of a single crystal silicon ingot during an exemplary continuous Czochralski growth method according to the present disclosure. As shown in FIG. 4A, a constant pull rate is maintained throughout a substantial portion of the growth of the main body of the single crystal silicon ingot. The line defined by the triangles (---▲---) is the critical pull rate that achieves the critical v / G value, which has an initial varying region followed by a region of constant pull rate throughout a substantial portion of the growth of the main body of the single crystal silicon ingot. The pull rate may be varied within an upper critical pull rate ("UCL") indicated by squares (---■---), and a lower critical pull rate ("LCL") indicated by diamonds (---◆---), and still achieve acceptable defectivity control. The areas of native point defects and agglomerated point defects in the cross-sectional area of ​​a single crystal silicon ingot are substantially the same as those described above in the description of FIG. 2A.

[0036] In the CCZ process according to the disclosed method, the polycrystalline silicon feed is continuous with the growing crystal, so that the melt volume remains substantially the same as the initial input melt depth regardless of the crystal length. Since the melt elevation is controlled by the mass balance between the growing crystal weight and the continuously fed polycrystalline silicon, the thermal conditions and temperature in the melt and the growing crystal remain constant throughout the axial growth. Then, once the desired crystal / melt interface is reached, the melt elevation is controlled by the mass balance between the growing crystal weight and the continuously fed polycrystalline silicon. magnetic field Once determined and fixed by parameters such as C / R and S / R, pulling speed, heater power, etc., the defect quality and O iControl will be maintained constant throughout the growth of the crystal axis. Furthermore, because the thermal conditions and crystal / melt interface are fixed during crystal growth, a constant pull rate for a given HZ and crystal / melt interface can be used over the entire crystal length in guasi-steady state control.

[0037] According to the method of the present disclosure, suitable thermal conditions to achieve the growth of a single crystal silicon ingot that meets the requirements for defectivity control are set by a hot zone configuration. The growth method is a continuous Czochralski process. Thus, the furnace chamber includes a means for a continuous supply of polycrystalline silicon, e.g., a feed tube. Although chunk polysilicon may be used, the solid polysilicon added to the crucible is typically granular polysilicon, which is fed to the crucible using a polysilicon feeder optimized for use with granular polysilicon. Chunk polysilicon typically has a size of 3-45 millimeters (e.g., largest dimension), and granular polysilicon typically has a size of 400-1400 microns. Granular polysilicon has several advantages, including providing easy and precise control of the feed rate due to its smaller size. However, the cost of granular polysilicon is typically higher than that of chunk polysilicon due to the chemical vapor deposition process or other manufacturing method used to produce it. Chunk polysilicon has the advantage of being cheaper and allowing a higher feed rate given its larger size. Adjust the position of the heating unit, the cooling jacket and the operation of the power controls to accommodate the polysilicon feeder.

[0038] A depiction of a crucible 10 having multiple weirs (20, 30, 40) or fluid barriers that separate the melt into different melt zones is shown in FIG. 5. In the illustrated embodiment, the crucible assembly 10 includes a first weir 20 (broadly, a fluid barrier) that defines an inner melt zone 22 of the silicon melt. The inner melt zone 22 is a growth region for growing a monocrystalline silicon ingot 50. A second weir 30 defines an intermediate melt zone 32 of the silicon melt. Finally, a third weir 40 defines an outer melt zone 42 of the silicon melt. A feed tube (not shown) delivers polycrystalline silicon, which may be grains, chunks, or a combination of grains and chunks, to the outer melt zone 42 at a rate sufficient to maintain a substantially constant melt height level and volume during ingot growth. Each of the first weir 20, second weir 30 and third weir 40 has a generally annular shape and at least one opening defined therein to allow molten silicon to flow radially inward toward the growth region of the inner melt zone 22. The crucible configuration shown in FIG. 5 is exemplary and suitable for carrying out the process of the present disclosure. Other configurations suitable for the CCZ may be used without departing from the scope of the present disclosure. For example, the crucible 10 may lack the second weir 30 and / or may lack the third weir 40.

[0039] Typically, the melt from which the ingot is removed is formed by loading polycrystalline silicon into a crucible to form an initial silicon charge. Typically, the initial charge is about 100 kilograms to about 400 kilograms of polycrystalline silicon, for example, about 100 kilograms to about 300 kilograms of polycrystalline silicon or about 100 kilograms to about 200 kilograms of polycrystalline silicon, which may be grains, chunks, or a combination of grains and chunks. The mass of the initial charge depends on the desired crystal diameter and HZ design. Since polycrystalline silicon is continuously fed during crystal growth, the initial charge does not reflect the crystal length. For example, if polycrystalline silicon is continuously fed and the chamber height is high enough, the crystal length can extend to 2000 mm, 3000 mm, or even 4000 mm in length. The crucible may have the configuration shown in FIG. 5 or another configuration suitable for CCZ growth. Polycrystalline silicon from a variety of sources may be used, including, for example, granular polycrystalline silicon produced by the pyrolysis of silanes or halosilanes in a fluidized bed reactor, or polycrystalline silicon produced in a Siemens reactor.

[0040] In some embodiments, the melt is further charged with a nitrogen source so that the single crystal silicon ingot grown by the methods of the present disclosure is doped with nitrogen. In some embodiments, the nitrogen source is a solid source of nitrogen, such as silicon nitride. Silicon nitride has the chemical formula Si X N Y where X and Y are both 1, or one or both of X and Y are greater than 1. Any form of silicon nitride may be used, Si 3 N 4is the most common and stable. Silicon nitride can be in granular or powder form. In some embodiments, the nitrogen source is a silicon wafer having a silicon nitride film on its surface. The silicon nitride film can also be deposited on the silicon wafer by chemical vapor deposition, for example, a 0.5 to 10 micrometer thick film, for example, about 1 micrometer thick film, on one or both sides of the wafer. The silicon wafer can be added in whole or it can be broken into small pieces. In some embodiments, the nitrogen source is silicon oxynitride glass. In some embodiments, the nitrogen doping is performed by doping with nitrogen (N 2 This can be accomplished by doping the polycrystalline silicon with a nitrogen-containing gas, such as nitrogen-containing nitrogen gas. To form the initial charge, the nitrogen source can be added directly to the polycrystalline silicon charge if a solid source is used. As the single crystal silicon ingot grows, the nitrogen source is added periodically or continuously to maintain a uniform concentration of nitrogen in each portion of the single crystal silicon ingot.

[0041] The disclosed method allows for uniform nitrogen concentrations in each portion of the growing single crystal silicon ingot, including the neck, the outwardly extending seed cone, and the body of the single crystal silicon ingot. In some embodiments, the nitrogen concentration in each portion of the growing single crystal silicon ingot is at least about 1×10 13 atoms / cm 3 , for example, about 1 x 10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or approximately 1 × 10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3Preferably, the change in nitrogen concentration is not more than about 20% more than and not less than 20% less than the set point or average nitrogen concentration over the axial length of the single crystal silicon ingot. More preferably, the change in nitrogen concentration is not more than about 10% more than and not less than 10% less than the set point or average nitrogen concentration over the axial length of the single crystal silicon ingot. Even more preferably, the change in nitrogen concentration is not more than about 5% more than and not more than 5% less than the set point or average nitrogen concentration over the axial length of the single crystal silicon ingot. For example, when the set point, i.e., target, nitrogen concentration is 7×10 13 atoms / cm 3 then, preferably, the concentration of nitrogen throughout the axial length of the single crystal silicon ingot is about 5.67×10 13 atoms / cm 3 ~Approx. 8.47×10 13 atoms / cm 3 , more preferably about 6.3 x 10 13 atoms / cm 3 ~Approx. 7.7×10 13 atoms / cm 3 , and even more preferably about 6.65×10 13 atoms / cm 3 ~Approx. 7.35×10 13 atoms / cm 3See FIG. 4B, which is a graph showing the nitrogen concentration uniformity (line defined by open circles ○) that can be achieved by periodic or continuous addition of nitrogen during a typical continuous Czochralski growth according to the method of the present disclosure. The uniformity can be compared to the increase in nitrogen concentration observed during a batch growth process (line defined by filled circles ●). See FIG. 2C. Preferably, a uniform nitrogen concentration is achieved during growth of all parts, including the neck, the outwardly extending seed cone, and the body of the ingot. In some embodiments, a uniform nitrogen concentration is achieved during growth of at least 40% of the body axis length of the single crystal silicon ingot, at least 50% of the body axis length of the single crystal silicon ingot, at least 60% of the body axis length of the single crystal silicon ingot, at least 70% of the body axis length of the single crystal silicon ingot, or at least 80% of the body axis length of the single crystal silicon ingot, or at least 90% of the body axis length of the single crystal silicon ingot.

[0042] Once the polycrystalline silicon and nitrogen source are added to the crucible to form a charge, the charge is heated to a temperature above about the melting temperature of silicon (e.g., about 1412°C) to melt the charge, thereby forming a silicon melt comprising molten silicon. The silicon melt has an initial volume of molten silicon and an initial melt height level, these parameters being determined by the size of the initial charge. In some embodiments, the crucible containing the silicon melt is heated to a temperature of at least about 1425°C, at least about 1450°C, or even at least about 1500°C. The silicon melt further comprises at least about 1×10 13 Nitrogen atoms / cm 3 In some embodiments, the silicon melt further comprises a nitrogen source sufficient to provide a nitrogen dopant concentration in the neck of the ingot of about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or approximately 1 × 10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 1013 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 The nitrogen dopant concentration in the neck portion of the ingot is sufficient to provide a nitrogen dopant concentration in the neck portion of the ingot of 0.1 to 0.5%.

[0043] Generally, there is no limitation on the resistivity of the single crystal silicon ingot. Thus, the resistivity of the single single crystal silicon ingot is based on the requirements of the final use / application of the structure of the present disclosure. Thus, the resistivity can vary from sub-milliohms to megaohms or more. In some embodiments, the crucible is doped with p-type or n-type dopants. Suitable dopants include boron (p-type), gallium (p-type), phosphorus (n-type), antimony (n-type), and arsenic (n-type). The dopant concentration is selected based on the desired resistivity of the wafer sliced ​​from the single crystal silicon ingot.

[0044] In some embodiments, the single crystal silicon ingots pulled by the methods of the present disclosure have a relatively low minimum bulk resistivity, such as less than about 100 ohm-cm, less than about 50 ohm-cm, less than about 1 ohm-cm, less than about 0.1 ohm-cm, or even less than about 0.01 ohm-cm. In some embodiments, the single crystal silicon ingots have a relatively low minimum bulk resistivity, such as less than about 100 ohm-cm, or between about 1 ohm-cm and about 100 ohm-cm. The low resistivity wafers can include electrically active dopants, such as boron (p-type), gallium (p-type), phosphorus (n-type), antimony (n-type), and arsenic (n-type). In some embodiments, the dopants are added to the initial charge in the crucible, and resistivity uniformity is maintained by continuous or periodic addition of dopants during crystal growth.

[0045] In some embodiments, the single crystal silicon ingot has a relatively high minimum bulk resistivity. Electrically active dopants such as boron (p-type), gallium (p-type), aluminum (p-type), indium (p-type), phosphorus (n-type), antimony (n-type), and arsenic (n-type) can be added in the crucible, typically in very low concentrations. Cz-grown silicon wafers can also be subjected to thermal annealing at temperatures ranging from about 600° C. to about 1000° C. to annihilate thermal donors caused by oxygen incorporated during crystal growth. In some embodiments, the single crystal silicon ingot has a ohm-cm of at least 100, at least about 500, at least about 1000, or even at least about 3000, such as from about 100 ohm-cm to about 100,000 ohm-cm, or from about 500 ohm-cm to about 100,000 ohm-cm, or from about 1000 ohm-cm to about 100,000 ohm-cm. The monocrystalline silicon ingot may have a minimum bulk resistivity of about 500 ohm-cm to about 10,000 ohm-cm, or about 750 ohm-cm to about 10,000 ohm-cm, about 1000 ohm-cm to about 10,000 ohm-cm, about 2000 ohm-cm to about 10,000 ohm-cm, about 3000 ohm-cm to about 10,000 ohm-cm, or about 3000 ohm-cm to about 5,000 ohm-cm. In some embodiments, the monocrystalline silicon ingot may include a p-type dopant, such as boron, gallium, aluminum, or indium. In some embodiments, the monocrystalline silicon ingot may include an n-type dopant, such as phosphorus, antimony, or arsenic. In some embodiments, dopants are added to the initial charge in the crucible and resistivity uniformity is maintained by continuous or periodic addition of dopants during crystal growth.For example, in some embodiments, the body portion has a resistivity that varies no more than 20% above and more than 20% below the average body resistivity over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot. In some embodiments, the body portion has a resistivity that varies no more than 10% above and more than 10% below the average body resistivity over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot. In some embodiments, the body portion has a resistivity that varies no more than 5% above and no more than 5% below the average body resistivity over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot.

[0046] Once the charge is liquefied to form a silicon melt containing molten silicon, the silicon seed is lowered into contact with the melt. The silicon seed is then removed from the melt attached thereto (i.e., with reference to FIG. 5, the seed portion and neck 52), thereby forming a melt / solid interface near or at the surface of the melt. Typically, the initial pull speed to form the neck is high. In some embodiments, the silicon seed and neck are pulled at a neck pull speed of at least about 1.0 mm / min, e.g., about 1.5 mm / min to about 6 mm / min, e.g., about 3 mm / min to about 5 mm / min. In some embodiments, the silicon seed and crucible rotate in opposite directions (i.e., counter-rotation). The counter-rotation achieves convection in the silicon melt. The rotation of the crystal is primarily used to provide a symmetrical temperature profile, suppress angular variations of impurities, and control the crystal-melt interface shape. In some embodiments, the silicon seed crystal is rotated at a speed of about 5 rpm to about 30 rpm, or about 5 rpm to about 20 rpm, or about 8 rpm to about 20 rpm, or about 10 rpm to about 20 rpm. In some embodiments, the crucible is rotated at a speed of about 0.5 rpm to about 10 rpm, or about 1 rpm to about 10 rpm, or about 4 rpm to about 10 rpm, or about 5 rpm to about 10 rpm. In some embodiments, the seed crystal is rotated at a speed that is at least 1 rpm higher than the rotation speed of the crucible, for example, at least 3 rpm higher, or at least 5 rpm higher. Typically, the crystal rotation speed is higher than the crucible rotation speed to favor good radial uniformity of the dopant concentration in the crystal. In some embodiments, the silicon seed crystal and the crucible are rotated in opposite directions (i.e., counter-rotating).

[0047] Typically, the neck portion has a length of about 10 mm to about 700 mm, about 30 mm to about 700 mm, about 100 mm to about 700 mm, about 200 mm to about 700 mm, or about 300 mm to about 700 mm. In some embodiments, the neck portion has a length of about 10 mm to about 100 mm, for example, about 20 to about 50 mm. In some embodiments, the neck portion has a length of about 350 mm to about 550 mm. In some embodiments, the neck portion has a length of about 450 mm to about 550 mm. However, the length of the neck portion can vary outside of these ranges. In some embodiments, the neck portion has a diameter of about 1 mm to about 10 mm, about 2.5 mm to about 6.5 mm, for example, about 3 mm to about 6 mm. Since the silicon melt is doped with nitrogen, the neck portion 52 of the ingot is doped with nitrogen. In some embodiments, the neck portion 52 has a diameter of at least about 1×10 13 atoms / cm 3 In some embodiments, neck portion 52 has a nitrogen concentration of about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or approximately 1 × 10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 Preferably, the change in nitrogen concentration is no more than about 20% greater and no less than about 20% less than the set point or average nitrogen concentration over the axial length of the neck. More preferably, the change in nitrogen concentration is no more than about 10% greater and no less than about 10% less than the set point or average nitrogen concentration over the axial length of the neck. Even more preferably, the change in nitrogen concentration is no more than about 5% greater and no less than about 5% less than the set point or average nitrogen concentration over the axial length of the neck.

[0048] After the formation of the neck, with reference to FIG. 5, an outwardly flaring seed cone portion 54 adjacent the neck 52 is grown. Typically, the pull rate is reduced from the neck pull rate to a rate appropriate for growing the outwardly flaring seed cone portion. For example, the seed cone pull rate during growth of the outwardly flaring seed cone is about 0.5 mm / min to about 2.0 mm / min, e.g., about 1.0 mm / min. In some embodiments, the outwardly flaring seed cone has a length of about 100 mm to about 400 mm, e.g., about 150 mm to about 250 mm. The length of the outwardly flaring seed cone 54 can vary outside of these ranges. In some embodiments, the outwardly flaring seed cone 54 is grown to a terminal diameter of about 150 mm, at least about 150 mm, about 200 mm, at least about 200 mm, about 300 mm, at least about 300 mm, about 450 mm, or even at least about 450 mm. The end diameter of the outwardly extending seed cone 54 is generally equivalent to the diameter of the constant diameter of the body of the single crystal silicon ingot. According to the method of the present disclosure, the outwardly extending seed cone 54 of the ingot is doped with nitrogen. In some embodiments, the outwardly extending seed cone 54 is doped with at least about 1×10 13 atoms / cm 3 In some embodiments, the outwardly extending seed cone 54 has a nitrogen concentration of about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3Preferably, the variation in nitrogen concentration in the outwardly extending seed cone 54 is about 20% or less and 20% or more less than the setpoint nitrogen concentration. More preferably, the variation in nitrogen concentration in the outwardly extending seed cone 54 is about 10% or less and 10% or more less than the setpoint nitrogen concentration. Even more preferably, the variation in nitrogen concentration in the outwardly extending seed cone 54 is about 5% or less and 5% or more less than the setpoint nitrogen concentration. Again, with reference to FIG. 4B, nitrogen concentration uniformity is preferably achieved by an exemplary method according to the present disclosure during growth of all portions of the ingot, including the outwardly extending seed cone.

[0049] An ingot body 56 is then grown having a constant diameter adjacent the cone portion after formation of the neck and the outwardly extending seed cone. The constant diameter portion of the body 56 has a peripheral edge, a central axis parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge. The central axis also passes through the cone portion and the neck 52. The diameter of the ingot body can vary, and in some embodiments the diameter can be about 150 mm, at least about 150 mm, about 200 mm, at least about 200 mm, about 300 mm, at least about 300 mm, about 450 mm, or even at least about 450 mm. In some embodiments, the single crystal silicon ingot body is eventually grown to be at least about 1000 millimeters long, e.g., at least 1100 millimeters long, e.g., at least 1200 millimeters long, e.g., at least 1400 millimeters long, e.g., at least 1500 millimeters long, e.g., at least 1700 millimeters long, or at least 1900 millimeters long, or at least 2000 millimeters long, or at least 2200 millimeters long, or at least about 3000 millimeters long, or at least about 4000 millimeters long. According to the method of the present disclosure, the ingot body 56 is doped with nitrogen. In some embodiments, the body 56 is doped with at least about 1×10 13 atoms / cm 3 In some embodiments, the body 56 has a body nitrogen concentration of about 1×1013 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or approximately 1 × 10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3Preferably, the variation in nitrogen concentration in the body 56 is about 20% or less and 20% or more less than the setpoint nitrogen concentration. More preferably, the variation in nitrogen concentration in the body 56 is about 10% or less and 10% or more less than the setpoint nitrogen concentration. Even more preferably, the variation in nitrogen concentration in the body 56 is about 5% or less and 5% or more less than the setpoint nitrogen concentration. Again, with reference to FIG. 4B, nitrogen concentration uniformity is preferably achieved by an exemplary method according to the present disclosure during growth of all portions of the ingot, including the main body portion. In some embodiments, the body comprises nitrogen with a body nitrogen concentration that varies no more than 20% above and more than 20% below the average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot. In some embodiments, the body comprises nitrogen with a body nitrogen concentration that varies by no more than 10% above and more than 10% below the average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot.In some embodiments, the body comprises nitrogen with a body nitrogen concentration that varies by no more than 5% above and by no less than 5% below the average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot.

[0050] 4A shows a typical and non-limiting pull rate protocol for pulling the body of a single crystal silicon ingot according to some embodiments of the method of the present disclosure. As is evident from the typical illustration, the pull rate is decreased from a relatively high pull rate to a minimum pull rate, and then increased to a constant pull rate for a significant portion of the growth of the body of the single crystal silicon ingot. According to the process of the present disclosure, the pull rate is selected to achieve perfect silicon, i.e., silicon characterized by a lack of detectable agglomerated defects selected from agglomerated defects, DSOD (direct surface oxidation defects), COP (crystal origin pits), D defects, and I defects, etc. The initial high pull rate can be about 0.5 mm / min to about 2.0 mm / min, for example, about 1.0 mm / min, then decreases to a pull rate that can be as low as about 0.4 mm / min or as low as about 0.3 mm / min, and then increases to a constant pull rate of about 0.4 mm / min to about 0.8 mm / min, about 0.4 mm / min to about 0.7 mm / min, or about 0.4 mm / min to about 0.65 mm / min.

[0051] Exemplary and non-limiting examples of hot zone configurations in the furnace chamber 100 suitable for carrying out the method of the present disclosure are shown in Figures 6A, 6B and 6C. Other hot zone configurations are suitable for carrying out the method of the present disclosure. The hot zone configuration includes a cooling jacket 102, a reflector 104, a side heater 106 and a bottom heater 108. The growing crystal diameter and the shape and height of the meniscus are monitored by a camera (not depicted) located at the top window. Data obtained from the camera allows feedback to the side heater 106 and the bottom heater 108. During crystal growth, the power distribution can be adjusted between the heaters to allow uniformity of the melt / solid interface, i.e., to maintain the desired shape and height of the meniscus. The reflector 104 will reflect the heat flow from the hot parts of the furnace, including the heaters and the crucible, to the melt. The reflector 104 reduces heat transfer from the hot portion of the furnace to the cooler portion (maintained by the cooling jacket 102), thereby maintaining separation between these two regions of the furnace. The reflector helps control the axial and radial temperature gradients that drive the solidification and crystallization of the molten silicon into the growing ingot.

[0052] 6A, 6B, and 6C show a first step, a second step, and a third step, respectively, which correspond to the regions of the pulling rate shown in FIG. 4A. That is, the first step shown in FIG. 6A corresponds to the region in FIG. 4A where the pulling rate is high and decreases to a minimum. The second step shown in FIG. 6B corresponds to the region in FIG. 4A where the pulling rate is minimum and increases to a constant pulling rate. The third step shown in FIG. 6C corresponds to the region in FIG. 4A of constant pulling rate. During each step, the melt 110 maintains a constant melt volume and melt height level according to an embodiment of the present disclosure, as polycrystalline silicon is continuously fed to the melt during the growth of the ingot 112 (see FIG. 5).

[0053] The initial region for growing the monocrystalline silicon ingot body characterized by the variable pull rate may encompass less than about 20% of the total length of the monocrystalline silicon ingot body. In some embodiments, the variable pull rate regime may encompass about 5% to about 20% of the monocrystalline silicon ingot body length, e.g., about 5% to about 15% of the monocrystalline silicon ingot body length, or about 10% to about 15% of the monocrystalline silicon ingot body length. The percentage of the monocrystalline silicon ingot body length grown under variable pull rate conditions depends in part on the total length of the ingot body. For example, the body length of the ingot pulled under variable rate conditions may vary from about 50 mm to about 200 mm, from about 100 mm to about 200 mm, e.g., from about 150 mm to about 200 mm. If 200 mm is grown under variable rate conditions and the total length of the body of the ingot is 1400 mm, then about 14% of the body is grown under variable rate conditions, while only about 9% of the body is grown under variable rate conditions for a total body length of 2200 mm.

[0054] After an initial region of the body is grown under variable pull rate conditions, the remainder of the body is grown under a constant pull rate. In some embodiments, the body of the ingot is grown at a constant body pull rate during growth of at least about 30% of the length of the single crystal silicon ingot, e.g., at least about 50% of the length of the single crystal silicon ingot, at least about 70% of the length of the single crystal silicon ingot, at least about 80% of the length of the single crystal silicon ingot, or even at least about 90% of the length of the single crystal silicon ingot. In some embodiments, the constant body pull rate is between about 0.4 mm / min and about 0.8 mm / min, between about 0.4 mm / min and about 0.7 mm / min, or between about 0.4 mm / min and about 0.65 mm / min.

[0055] During the growth of the body of the monocrystalline silicon ingot, polycrystalline silicon, i.e., grains, chunks, or a combination of grains and chunks, is added to the molten silicon, thereby achieving a constant volume of molten silicon and a constant melt height level. According to the method of the present disclosure, maintaining a substantially constant melt volume during the growth of a substantial portion of the body axial length of the monocrystalline silicon ingot allows for the achievement of high ingot quality over a substantial portion of the body axial length of the monocrystalline silicon ingot at a constant pull rate. A constant melt volume regardless of the crystal length allows for a constant crystal / melt interface, thus allowing for uniform crystal quality over a substantial portion of the body of the ingot. Thus, in some embodiments, the volume of molten silicon varies by about 1.0 vol.% or less during the growth of at least 90% of the body of the monocrystalline silicon ingot, or by about 0.5 vol.% or less during the growth of at least 90% of the body of the monocrystalline silicon ingot, or by about 0.1 vol.% or less during the growth of at least 90% of the body of the monocrystalline silicon ingot. Stated another way, in some embodiments, the melt height level varies by less than about + / - 0.5 millimeters during the growth of at least 90% of the body of the single crystal silicon ingot.

[0056] During growth of the body of the single crystal silicon ingot, the melt is further charged with a nitrogen source so that the single crystal silicon ingot grown by the method of the present disclosure is doped with nitrogen. In some embodiments, the nitrogen source is a solid source of nitrogen, such as silicon nitride. The silicon nitride can be in the form of a powder. In some embodiments, the nitrogen source is a silicon wafer having a silicon nitride film on its surface. The silicon nitride film can be deposited on the silicon wafer by chemical vapor deposition to deposit a film, for example, 0.5 to 10 micrometers, e.g., about 1 micrometer, thick on both sides of the wafer. The silicon wafer can be added in its entirety or it can be broken into small pieces. In some embodiments, the nitrogen source is a silicon oxynitride glass. In some embodiments, the nitrogen doping is performed using nitrogen (N 2During growth of the ingot, according to the method of the present disclosure, a nitrogen source may be added to the polycrystalline silicon in a third weir 40, as shown in FIG.

[0057] The disclosed method is suitable for achieving axially uniform nitrogen concentration during the growth of the neck, seed cone and body of a single crystal silicon ingot. See FIG. 4B for a depiction of the uniformity that may be achieved by continuous or periodic addition of nitrogen during the growth of an ingot by the disclosed continuous Czochralski technique. Uniformity that overcomes the segregation typically found in nitrogen doped single crystal silicon ingots is achieved by an automated doping system that continuously or periodically adds a nitrogen source to the melt. The nitrogen source may be added continuously or periodically during the growth of the ingot, including each of the neck, seed cone and body. Also, in some embodiments, for process uniformity and ease, periodic addition of a nitrogen source during, for example, every 25 mm, 50 mm, 75 mm, or 100 mm of axial length during ingot growth is preferred to enhance the achievement of full silicon during the growth of the ingot axial length.

[0058] In some embodiments, the nitrogen source is continuously or periodically supplied to the crucible in an amount of about 1 milligram of nitrogen to about 100 milligrams of nitrogen per 50 mm axial length of the body of the single crystal silicon ingot, about 1 milligram of nitrogen to about 25 milligrams of nitrogen per 50 mm axial length of the body of the single crystal silicon ingot, or about 2 milligrams of nitrogen to about 15 milligrams of nitrogen per 50 mm axial length of the body of the single crystal silicon ingot. In some embodiments, the nitrogen source is silicon nitride, which may be added as a powder. In some embodiments, silicon nitride is continuously or periodically fed to the crucible during growth of the single crystal silicon ingot body in an amount of about 2.5 milligrams of silicon nitride to 250 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body, or about 5 milligrams of silicon nitride to 100 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body, or about 10 milligrams of silicon nitride to 50 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body. In some exemplary embodiments, about 10 milligrams to about 50 milligrams of silicon nitride, e.g., about 25 milligrams of silicon nitride, may be added per 50 mm of axial length of a body having a nominal diameter of about 310 millimeters. The amount of silicon nitride added may be adjusted up or down depending on the nominal diameter of the ingot. For example, about 1 milligram to about 10 milligrams, e.g., about 5 or 6 milligrams, of silicon nitride may be added per 50 mm axial length of a body having a nominal diameter of about 150 millimeters. In yet another example, about 25 milligrams to about 75 milligrams, e.g., about 45 milligrams to about 60 milligrams, of silicon nitride may be added per 50 mm axial length of a body having a nominal diameter of about 450 millimeters. A typical feeding protocol showing the total silicon nitride addition as a function of the axial length of a single crystal silicon ingot is shown in FIG.

[0059] In some embodiments, a nitrogen source is added during growth to provide about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm3 , or approximately 1 × 10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 In some embodiments, a nitrogen source is added during growth to achieve a bulk nitrogen concentration of about 5×10 over at least 40% of the monocrystalline silicon ingot's axial length, over at least 50% of the monocrystalline silicon ingot's axial length, over at least 60% of the monocrystalline silicon ingot's axial length, over at least 70% of the monocrystalline silicon ingot's axial length, or over at least 80% of the monocrystalline silicon ingot's axial length, or over at least 90% of the monocrystalline silicon ingot's axial length, or even over the entire monocrystalline silicon ingot's axial length. 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 Achieve a nitrogen concentration of

[0060] In some embodiments, a nitrogen source is added during growth to provide about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5 × 10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3and further wherein the body nitrogen concentration varies by no more than 20% above and no less than 20% below the set point or average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot, or even over the entire axial length of the single crystal silicon ingot. More preferably, the change in nitrogen concentration in the body 56 is no more than about 10% greater and no less than 10% less than the setpoint nitrogen concentration over at least 40% of the axial length of the single crystal silicon ingot, over at least 50% of the axial length of the single crystal silicon ingot, over at least 60% of the axial length of the single crystal silicon ingot, over at least 70% of the axial length of the single crystal silicon ingot, or over at least 80% of the axial length of the single crystal silicon ingot, over at least 90% of the axial length of the single crystal silicon ingot, or even over the entire axial length of the single crystal silicon ingot body. Even more preferably, the change in nitrogen concentration in the body 56 is no more than about 5% greater and no less than 5% less than the setpoint nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot, or even over the entire axial length of the single crystal silicon ingot body.

[0061] In some embodiments, a nitrogen source is added during growth to provide about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3and further wherein the body nitrogen concentration varies by no more than 20% above and by no less than 20% below the set point or average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot. More preferably, the change in nitrogen concentration in the body 56 is no more than about 10% greater and no less than 10% less than the setpoint nitrogen concentration over at least 40% of the axial length of the single crystal silicon ingot, over at least 50% of the axial length of the single crystal silicon ingot, over at least 60% of the axial length of the single crystal silicon ingot, over at least 70% of the axial length of the single crystal silicon ingot, or over at least 80% of the axial length of the single crystal silicon ingot, or over at least 90% of the axial length of the single crystal silicon ingot, or even over the entire axial length of the single crystal silicon ingot body. Even more preferably, the change in nitrogen concentration in the body 56 is no more than about 5% greater and no less than 5% less than the setpoint nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot, or even over the entire axial length of the single crystal silicon ingot body.

[0062] In addition, according to the process of the present disclosure: magnetic field may be applied to a crucible containing silicon melt. Cusp or horizontal magnetic field (or, magnetic fieldA magnet field can be applied to set the appropriate crystal / melt interface, i.e., meniscus, shape and height. magnetic field The desired crystal / melt interface shape and height are first fixed using the oxygen content O i Control of the is a subordinate objective.

[0063] Control of the melt flow and the shape of the melt / solid interface, and therefore the quality of the ingot, depends on the influence of the silicon melt during the growth of the main body of the monocrystalline silicon ingot. magnetic field In some embodiments, the applied magnetic field maintains a substantially constant melt / solid interface profile during at least about 70% of the growth of the body of the single crystal silicon ingot, or between about 70% and about 90% of the growth of the body of the single crystal silicon ingot. magnetic field applies electromagnetic forces that affect the silicon melt flow and therefore the heat transfer in the melt, which changes the crystal / melt interface profile and the temperature at which the crystal grows, which are the key control parameters for perfect silicon.

[0064] magnetic field strongly influences the oxygen content and uniformity of the ingot. The oxygen sources in the ingot are the melting of the quartz crucible walls, evaporation of the melt-free surface (controlled by melt flow dynamics), and the i O x (g) and from incorporation onto the growing crystal surface. magnetic field can strongly affect the conductive melt flow during growth, which in turn can strongly affect oxygen evaporation and incorporation. The change in oxygen incorporation into a single crystal silicon ingot with time increment can be expressed by the following equation:

[0065]

number

[0066] where C is the oxygen concentration of the solidifying silicon, t is time, v is the convection velocity (melt flow velocity), ρ (rho) is the density of the silicon melt, and ∇ is the gradient (d / dx). magnetic field affects the melting rate (v) and the gradient of the oxygen concentration in the melt (dC / dx=∇C). magnetic field As a result, a steady state melt flow occurs, and oxygen (O i The uptake of oxygen is a time constant, which enhances the radial and axial oxygen concentration uniformity. The term SOURCE is a function of two parameters: oxygen generation (S i (l)+S i O 2 (s) → S i O x (g)) is quartz (S i O 2 ) melting of the crucible and oxygen (S i O x The term SOURCE comes from evaporation, which is the removal (loss) of oxygen (g) from the solidifying silicon crystal. In the batch Cz process, this term SOURCE is not constant. Instead, it depends on the crystal length, since the melt mass decreases as the crystal grows. When the ingot has grown a substantial portion of its body length, the remaining melt volume is low, and as a result, the amount of silicon melt in contact with the crucible decreases, thus leading to a lower oxygen concentration taken up by the melt from the crucible. Thus, if other terms (diffusion, convection, evaporation) are constant, less oxygen is incorporated into the solidifying silicon crystal. The melt-free surface area (the contact surface between the melt and the gas) is S i O x (g) affects the evaporation rate. The small melt mass in the batch Cz process has a relatively smaller surface area due to the crucible shape shown in FIG. 1C. i O x Less evaporation of (g) means more oxygen incorporation into the solidifying silicon crystal. According to the method of the present disclosure, as polysilicon is added to grow the crystal ingot, the melt mass remains constant. Therefore, all the source terms (S i O 2Oxygen generation from crucible melting and S through the melt-free surface i O x (g) Evaporation of gases) is constant. Therefore, the terms diffusion and convection affect the oxygen in the solidifying silicon crystal. magnetic fieldThis makes the melt flow more stable since the oxygen incorporation is uniform and stable in the axial and radial directions during the growth of the entire length of the ingot (i.e., the melt flow is constant as in a time-independent steady state condition). In some embodiments, interstitial oxygen may be incorporated into the ingot at a concentration of about 4 PPMA to about 18 PPMA. In some embodiments, interstitial oxygen may be incorporated into the ingot at a concentration of about 10 PPMA to about 35 PPMA. In some embodiments, the ingot contains oxygen at a concentration of about 15 PPMA or less, or about 10 PPMA or less. Interstitial oxygen may be measured by SEMI MF 1188-1105. In some embodiments, the body interstitial oxygen concentration varies by no more than 20% above and by no less than 20% below the average body oxygen concentration over at least 40% of the body axis length of the single crystal silicon ingot, over at least 50% of the body axis length of the single crystal silicon ingot, over at least 60% of the body axis length of the single crystal silicon ingot, over at least 70% of the body axis length of the single crystal silicon ingot, or over at least 80% of the body axis length of the single crystal silicon ingot, or over at least 90% of the body axis length of the single crystal silicon ingot. In some embodiments, the body interstitial oxygen concentration varies by no more than 10% above and by no less than 10% below the average body oxygen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot.In some embodiments, the body interstitial oxygen concentration varies by no more than 5% above and by no less than 5% below the average body oxygen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot, or over at least 90% of the body axial length of the single crystal silicon ingot.

[0067] In some embodiments, the horizontal magnetic field is applied to the silicon melt during the growth of the body of a single crystal silicon ingot. Such a horizontal field is shown in Figure 8A, which is a horizontal field placed over the crucible and growing ingot, as shown in Figure 5. magnetic field This is a depiction of the horizontal magnetic field Crystal growth in the presence of a horizontal magnet is accomplished by placing a crucible that holds the silicon melt between the poles of a conventional electromagnet 200. magnetic field The magnetic flux density in the melt region may be about 0.2 Tesla to about 0.4 Tesla. magnetic field The variation is less than + / - about 0.03 Tesla for a given strength. magnetic field Application of the force creates a Lorentz force along the axial direction, opposite the direction of the fluid motion and countering the force driving the melt convection. Thus, convection in the melt is suppressed and the axial temperature gradient in the crystal near the interface increases. The melt-crystal interface then shifts upwards towards the crystal side to accommodate the increased axial temperature gradient in the crystal near the interface and the contribution from the melt convection in the crucible decreases.

[0068] In some embodiments, Cusp magnetic field is applied to the silicon melt during growth of the body of the single crystal silicon ingot. Cusp The field is shown in FIG. 8B, which is a 300 nm thick film placed over the crucible and growing ingot as shown in FIG. Cusp magnetic field This is a depiction of the situation. Cusp magnetic fieldis determined by two control parameters, namely, magnetic flux density and magnetic field It has a shape. Cusp magnetic field is the vertical (axis) in the melt near the axis of the ingot magnetic field and deeper, horizontal (radial) at the nearest surface of the combined melt magnetic field The components are applied. Cusp magnetic field is generated using a pair of Helmholtz coils carrying currents in opposite directions. As a result, two magnetic field At the midpoint of the ingot, perpendicular to the axis of the ingot, magnetic field cancel each other out, resulting in a vertical line at or near zero. magnetic field Create a component. For example, Cusp The magnetic flux density in the axial direction is typically about 0 to about 0.2 Tesla. The magnetic flux density in the radial direction is generally higher than the magnetic flux density in the perpendicular direction. For example, Cusp The magnetic flux density is typically about 0 to about 0.6 T at a radial position, depending on the radial position, for example, about 0.2 to about 0.5 T. Cusp magnetic field The radial direction of the melt is suppressed, thereby stabilizing the melt. Cusp magnetic field The application of heat acts as an effective method to induce convection adjacent to the solid-liquid interface where crystal growth occurs and suppress convection in the remaining part of the melt, thereby achieving a uniform oxygen distribution. The melt convection of heat occurs simultaneously at the melt-free surface and at the melt crucible interface. Cusp magnetic field This allows control of the oxygen concentration in the growing crystal by magnetic flux density alone, regardless of the crystal rotation speed. magnetic field In the presence of, control of the oxygen concentration is achieved through control of the crystal rotation rate. Cusp magnetic field The applied voltage is about 15 PPMA or less, or about 10 PPMA or less. magnetic field This may allow growth on an ingot containing less oxygen than an ingot grown without interstitial oxygen. Interstitial oxygen may be measured by SEMI MF 1188-1105.

[0069] The disclosed method enables the growth of single crystal silicon ingots by a continuous Czochralski process that meets or exceeds industry specifications for perfect silicon. Factors that contribute to the growth of perfect silicon crystals include determining the critical pull rate for growing perfect silicon, maintaining a constant pull rate at the critical rate throughout a substantial portion of the growth of the body of the single crystal silicon ingot, and maintaining the shape and height of the melt / solid interface. magnetic field Once the pulling speed and magnetic field Once the configuration is determined, the pull rate can be maintained at a constant rate by continuously adding polycrystalline silicon to maintain a constant melt volume and melt height level. Thus, unlike conventional methods of growing ingots, the pull rate is constant over a substantial portion of the ingot's growth. In view of the process control enabled by the methods disclosed herein, the methods of the present disclosure enable the growth of single crystal silicon ingots that include full silicon over at least about 70% of the single crystal silicon ingot's body length, such as over at least about 80% of the single crystal silicon ingot's body length, or even over at least about 90% of the single crystal silicon ingot's body length.

[0070] As used herein, the terms "about," "substantially," "essentially," and "approximately," when used in conjunction with a range of a dimension, concentration, temperature, or other physical or chemical property or characteristic, are meant to cover variations that may exist at the upper and / or lower limits of the range of the property or characteristic, including, for example, variations that are due to rounding, measurement methodology, or other statistical variations.

[0071] When introducing elements of the disclosure or embodiments thereof, the terms "a," "an," "the," and "the" are intended to mean that there are one or more elements. The terms "comprising," "including," "containing," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements. The use of terms indicating a particular orientation (e.g., "top," "bottom," "side," etc.) is for convenience of description and does not require a particular orientation of any of the described items.

[0072] Since various changes can be made in the above-described structures and methods without departing from the scope of the disclosure, it is intended that all matter contained in the above specification and shown in the accompanying drawings be interpreted as illustrative and not in a limiting sense.

Claims

1. A method for producing a single crystal silicon ingot by a continuous Czochralski process, comprising the steps of: adding an initial charge of polycrystalline silicon to a crucible, said initial charge further comprising a nitrogen source; heating a crucible containing an initial charge of polycrystalline silicon and a nitrogen source to form a silicon melt in the crucible, wherein the silicon melt comprises an initial volume of molten silicon and has an initial melt height level; contacting a silicon seed crystal with a silicon melt; pulling the silicon seed crystal to grow a neck portion, the silicon seed crystal being pulled at a neck pull rate during growth of the neck portion, and the neck portion having a thickness of at least about 1×10 13 atoms / cm 3 having a neck nitrogen concentration of pulling the silicon seed crystal to grow an outwardly extending seed cone adjacent the neck portion, the silicon seed crystal being pulled at a seed cone pull rate during growth of the outwardly extending seed cone, and further comprising: 13 atoms / cm 3 having a seed cone nitrogen concentration extending outside of the pulling the silicon seed crystal to grow a body of the single crystal silicon ingot adjacent an outwardly extending seed cone; the silicon melt comprising a volume of molten silicon and a melt height level during growth of the body of the single crystal silicon ingot; and further comprising: a volume of at least about 1×10 13 atoms / cm 3 having a body nitrogen concentration of The single crystal silicon ingot body is grown at an initial variable body pull rate and a constant body pull rate, the single crystal silicon ingot body being grown at the initial variable body pull rate for less than about 20% of the single crystal silicon ingot body length and being grown at the constant body pull rate for a growth of at least about 30% of the single crystal silicon ingot body length; and The method further comprises continuously or periodically supplying polycrystalline silicon to the crucible, thereby replenishing the volume of molten silicon in the crucible during growth of the main body of the single crystal silicon ingot, thereby maintaining a melt height level, and continuously or periodically supplying a nitrogen source to the crucible, thereby replenishing the amount of nitrogen.

2. The process of claim 1 , wherein the nitrogen source is a solid source of nitrogen.

3. The method of claim 1 , wherein the nitrogen source is silicon nitride powder.

4. 2. The method of claim 1, wherein the nitrogen source is a silicon wafer having a silicon nitride film on a surface thereof, the silicon wafer being optionally fractured.

5. The method of claim 1 wherein the nitrogen source is silicon oxynitride glass.

6. The process of claim 1 , wherein the nitrogen source is nitrogen gas.

7. The neck nitrogen concentration is about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 The method according to claim 1,

8. The outer seed corn nitrogen concentration is about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 The method according to claim 1,

9. 2. The method of claim 1, wherein the nitrogen source is continuously or periodically supplied to the crucible in an amount of about 1 milligram of nitrogen to about 100 milligrams of nitrogen per 50 mm of axial length of the body of the single crystal silicon ingot, about 1 milligram of nitrogen to about 25 milligrams of nitrogen per 50 mm of axial length of the body of the single crystal silicon ingot, or about 2 milligrams of nitrogen to about 15 milligrams of nitrogen per 50 mm of axial length of the body of the single crystal silicon ingot.

10. 2. The method of claim 1, wherein silicon nitride is continuously or periodically supplied to the crucible during growth of the single crystal silicon ingot body in an amount of about 2.5 milligrams of silicon nitride to 250 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body, or about 5 milligrams of silicon nitride to 100 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body, or about 10 milligrams of silicon nitride to 50 milligrams of silicon nitride per 50 mm of axial length of the single crystal silicon ingot body.

11. The body nitrogen concentration is about 1×10 13 atoms / cm 3 ~Approx. 1×10 15 atoms / cm 3 , or about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 The method according to claim 1,

12. the bulk nitrogen concentration is greater than or equal to about 5×10 over at least 40% of the body axis length of the single crystal silicon ingot, at least 50% of the body axis length of the single crystal silicon ingot, at least 60% of the body axis length of the single crystal silicon ingot, at least 70% of the body axis length of the single crystal silicon ingot, or at least 80% of the body axis length of the single crystal silicon ingot 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 The method according to claim 1,

13. The body nitrogen concentration is about 1×10 13 atoms / cm 3 ~Approx. 1.5×10 14 atoms / cm 3 , or about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 and further wherein the body nitrogen concentration varies no more than 20% above and no less than 20% below the average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot.

14. The body nitrogen concentration is about 5×10 13 atoms / cm 3 ~Approx. 1×10 14 atoms / cm 3 and further wherein the body nitrogen concentration varies no more than 20% above and no less than 20% below the average body nitrogen concentration over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot.

15. The method of claim 1 , wherein a magnetic field is applied to the silicon melt during growth of the body of the single crystal silicon ingot.

16. The method of claim 15 , wherein a horizontal magnetic field is applied to the silicon melt during growth of the main body of the single crystal silicon ingot.

17. The method of claim 15 , wherein a tip magnetic field is applied to the silicon melt during growth of the main body of the single crystal silicon ingot.

18. The method of claim 15 , wherein the applied magnetic field maintains a substantially constant melt / solid interface profile for at least about 70% of the growth of the body of the single crystal silicon ingot.

19. The method of claim 15, wherein the applied magnetic field maintains a substantially constant melt / solid interface profile during about 70% to about 90% of the growth of the body of the single crystal silicon ingot.

20. 2. The method of claim 1, wherein the body of the single crystal silicon ingot is at least about 1000 millimeters long, such as at least 1400 millimeters long, such as at least 1500 millimeters long, or at least 2000 millimeters long, or at least 2200 millimeters long, such as 2200 millimeters long, or at least about 3000 millimeters long, or at least about 4000 millimeters long.

21. 10. The method of claim 1, wherein the body of the single crystal silicon ingot has a diameter of at least about 150 millimeters, such as at least about 200 millimeters, at least about 300 millimeters, or at least about 450 millimeters.

22. 2. The method of claim 1, wherein the constant body pull rate is from about 0.4 mm / min to about 0.8 mm / min, from about 0.4 mm / min to about 0.7 mm / min, or from about 0.4 mm / min to about 0.65 mm / min.

23. The method of claim 1 , wherein the single crystal silicon ingot body is grown at an initial variable body pull rate for about 5% to about 20% of the single crystal silicon ingot body length.

24. The method of claim 1 , wherein the body of the single crystal silicon ingot is grown at a constant body pull rate during growth of at least about 50% of the length of the body of the single crystal silicon ingot.

25. The method of claim 1 , wherein the body of the single crystal silicon ingot is grown at a constant body pull rate during growth of at least about 70% of the length of the body of the single crystal silicon ingot.

26. The method of claim 1 , wherein the body of the single crystal silicon ingot is grown at a constant body pull rate during growth of at least about 80% of the length of the body of the single crystal silicon ingot.

27. The method of claim 1 , wherein the body of the single crystal silicon ingot is grown at a constant body pull rate during growth of at least about 90% of the length of the body of the single crystal silicon ingot.

28. The method of claim 1 , wherein the body pull rate is a constant critical pull rate sufficient to avoid agglomerated point defects over at least 70% of the body length of the single crystal silicon ingot.

29. The method of claim 1 , wherein the body pull rate is a constant critical pull rate sufficient to avoid agglomerated point defects over at least 90% of the body length of the single crystal silicon ingot.

30. The method of claim 1 , wherein the volume of molten silicon changes by no more than about 1.0 vol. % during growth of at least about 90% of the body of the single crystal silicon ingot.

31. The method of claim 1 , wherein the volume of molten silicon changes by no more than about 0.5 vol. % during growth of at least about 90% of the body of the single crystal silicon ingot.

32. The method of claim 1 , wherein the volume of molten silicon changes by no more than about 0.1 vol. % during growth of at least about 90% of the body of the single crystal silicon ingot.

33. The method of claim 1 , wherein the melt height level varies by less than about + / −0.5 millimeters during growth of at least about 90% of the body of the single crystal silicon ingot.

34. The method of claim 1 , wherein the body of the single crystal silicon ingot comprises full silicon across at least about 70% of the length of the body of the single crystal silicon ingot.

35. The method of claim 1 , wherein the body of the single crystal silicon ingot comprises full silicon across at least about 80% of the length of the body of the single crystal silicon ingot.

36. The method of claim 1 , wherein the body of the single crystal silicon ingot comprises full silicon across at least about 90% of the length of the body of the single crystal silicon ingot.

37. 1. A single crystal silicon ingot having a body portion, 14. The monocrystalline silicon ingot of claim 13, wherein the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, and wherein wafers sliced ​​from any portion of the body spanning at least 60% of the monocrystalline silicon ingot's body axial length, spanning at least 70% of the monocrystalline silicon ingot's body axial length, or spanning at least 80% of the monocrystalline silicon ingot's body axial length are characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I defects (A defects) by Secco etch technique.

38. 38. The single crystal silicon ingot of claim 37, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the single crystal silicon ingot's body axis length, spanning at least 70% of the single crystal silicon ingot's body axis length, or spanning at least 80% of the single crystal silicon ingot's body axis length are characterized by less than 20 COPs at 0.026 μm size or less.

39. 38. The single crystal silicon ingot of claim 37, further comprising interstitial oxygen with a body oxygen concentration that varies no more than 20% above and more than 20% below the average body oxygen concentration over at least 40% of the single crystal silicon ingot's body axial length, over at least 50% of the single crystal silicon ingot's body axial length, over at least 60% of the single crystal silicon ingot's body axial length, over at least 70% of the single crystal silicon ingot's body axial length, or over at least 80% of the single crystal silicon ingot's body axial length.

40. 38. The single crystal silicon ingot of claim 37, further comprising nitrogen at a body nitrogen concentration that varies no more than 20% above and more than 20% below the average body nitrogen concentration over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

41. 38. The single crystal silicon ingot of claim 37, wherein the body portion has a resistivity that varies no more than 20% above and more than 20% below the average body resistivity over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

42. 1. A single crystal silicon ingot having a body portion, the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, the body portion comprising interstitial oxygen at a body oxygen concentration that varies no more than 20% above and more than 20% below an average body oxygen concentration across at least 40% of the body axial length of the single crystal silicon ingot, across at least 50% of the body axial length of the single crystal silicon ingot, across at least 60% of the body axial length of the single crystal silicon ingot, across at least 70% of the body axial length of the single crystal silicon ingot, or across at least 80% of the body axial length of the single crystal silicon ingot.

43. 43. The single crystal silicon ingot of claim 42, further comprising nitrogen at a body nitrogen concentration that varies no more than 20% above and more than 20% below the average body nitrogen concentration over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

44. 43. The single crystal silicon ingot of claim 42, wherein the body portion has a resistivity that varies no more than 20% above and more than 20% below the average body resistivity over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

45. 43. The monocrystalline silicon ingot of claim 42, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the monocrystalline silicon ingot's body axial length, spanning at least 70% of the monocrystalline silicon ingot's body axial length, or spanning at least 80% of the monocrystalline silicon ingot's body axial length are characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I defects (A defects) by Secco etch technique.

46. 43. The single crystal silicon ingot of claim 42, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the single crystal silicon ingot's body axis length, spanning at least 70% of the single crystal silicon ingot's body axis length, or spanning at least 80% of the single crystal silicon ingot's body axis length are characterized by less than 20 COPs at 0.026 μm size or less.

47. 1. A single crystal silicon ingot having a body portion, 14. The monocrystalline silicon ingot of claim 13, wherein the body portion has a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, and the body portion comprises nitrogen at a body nitrogen concentration that varies no more than 20% above and more than 20% below an average body nitrogen concentration along at least 40% of the body axial length of the monocrystalline silicon ingot, along at least 50% of the body axial length of the monocrystalline silicon ingot, along at least 60% of the body axial length of the monocrystalline silicon ingot, along at least 70% of the body axial length of the monocrystalline silicon ingot, or along at least 80% of the body axial length of the monocrystalline silicon ingot.

48. 48. The single crystal silicon ingot of claim 47, further comprising interstitial oxygen with a body oxygen concentration that varies no more than 20% above and more than 20% below the average body oxygen concentration over at least 40% of the single crystal silicon ingot's body axial length, over at least 50% of the single crystal silicon ingot's body axial length, over at least 60% of the single crystal silicon ingot's body axial length, over at least 70% of the single crystal silicon ingot's body axial length, or over at least 80% of the single crystal silicon ingot's body axial length.

49. 48. The single crystal silicon ingot of claim 47, wherein the body portion has a resistivity that varies no more than 20% above and more than 20% below an average body resistivity over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

50. 48. The monocrystalline silicon ingot of claim 47, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the monocrystalline silicon ingot's body axial length, spanning at least 70% of the monocrystalline silicon ingot's body axial length, or spanning at least 80% of the monocrystalline silicon ingot's body axial length are characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I defects (A defects) by Secco etch technique.

51. 48. The single crystal silicon ingot of claim 47, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the single crystal silicon ingot's body axis length, spanning at least 70% of the single crystal silicon ingot's body axis length, or spanning at least 80% of the single crystal silicon ingot's body axis length are characterized by less than 20 COPs at 0.026 μm size or less.

52. 1. A single crystal silicon ingot having a body portion, the body portion having a peripheral edge, a central axis having an axial length parallel to the peripheral edge, and a radius extending from the central axis to the peripheral edge, and further, the body portion having a resistivity that varies no more than 20% above and more than 20% below an average body resistivity over at least 40% of the body axial length of the single crystal silicon ingot, over at least 50% of the body axial length of the single crystal silicon ingot, over at least 60% of the body axial length of the single crystal silicon ingot, over at least 70% of the body axial length of the single crystal silicon ingot, or over at least 80% of the body axial length of the single crystal silicon ingot.

53. 53. The single crystal silicon ingot of claim 52, further comprising interstitial oxygen with a body oxygen concentration that varies no more than 20% above and more than 20% below the average body oxygen concentration over at least 40% of the single crystal silicon ingot's body axial length, over at least 50% of the single crystal silicon ingot's body axial length, over at least 60% of the single crystal silicon ingot's body axial length, over at least 70% of the single crystal silicon ingot's body axial length, or over at least 80% of the single crystal silicon ingot's body axial length.

54. 53. The single crystal silicon ingot of claim 52, further comprising nitrogen at a body nitrogen concentration that varies no more than 20% above and more than 20% below the average body nitrogen concentration over at least 40% of a body axial length of the single crystal silicon ingot, over at least 50% of a body axial length of the single crystal silicon ingot, over at least 60% of a body axial length of the single crystal silicon ingot, over at least 70% of a body axial length of the single crystal silicon ingot, or over at least 80% of a body axial length of the single crystal silicon ingot.

55. 53. The monocrystalline silicon ingot of claim 52, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the monocrystalline silicon ingot's body axial length, spanning at least 70% of the monocrystalline silicon ingot's body axial length, or spanning at least 80% of the monocrystalline silicon ingot's body axial length are characterized by no detectable FPD (flow pattern defects by Secco etch technique) and DSOD (direct surface oxide defect particle count after electrical breakdown), and zero I defects (A defects) by Secco etch technique.

56. 53. The single crystal silicon ingot of claim 52, wherein wafers sliced ​​from any portion of the body spanning at least 60% of the single crystal silicon ingot's body axis length, spanning at least 70% of the single crystal silicon ingot's body axis length, or spanning at least 80% of the single crystal silicon ingot's body axis length are characterized by less than 20 COPs at 0.026 μm size or less.

Citation Information

Patent Citations

  • Method of continuously pulling up silicon single crystal free from agglomerates of point defects

    JP2001089294A

  • Method for manufacturing nitrogen-doped silicon single crystal

    JP2006315869A

  • Method of manufacturing nitrogen-doped silicon single crystal

    JP2009249265A

  • Silicon single crystal wafer for IGBT and process for producing silicon single crystal wafer for IGBT

    WO2009025336A1

  • Process for suppressing the nucleation and / or growth of interstitial type defects by controlling the cooling rate through nucleation

    US20030196587A1